Il rovescio della scena: gli impliciti performativi delle politiche securitarie (Mantichora. Italian Journal of Performance Studies, 2020)
As performances coincide with showing doing, the meaning and function of performative acts or actions have to be found in their meaning, more than in their effective results. Starting from Cirese’s reflections about the hendyade doing/saying, and thanks to Kirshenblatt-Gimblett’s suggestion that things are slow events, things and actions such as those relative to prison and asylum seekers acceptance policies, may be read “as performances”. Schechner’s theory inspired an approach to Italian state policies concerning security that reveals how the official and Constitutional ends are counterdicted and replaced by an inertial extension of retributive concept of penal condition, on the one hand, and, on the other, by a formal reject opposed to migrants and asylum seekers demand, that leave them as disciplined labour force for the informal (illegal) economy. Read under the performance approach, the security policies do perpetuate an idea of humanity divided between rights bearers (we) and right ruled (the others).